Effect of Preadolescents’ Obesity on Inhibitory Control During Stop-Signal Task: A Functional EEG Network Study - Yuqin Li; Qian Yang; Yuxin Liu; Yutong Zheng; Jianfu Li; Chunli Chen; Baodan Chen; Dezhong Yao; Liang Yu; Peng Xu; Fali Li; Yi Liang (IEEE Open Journal of Engineering in Medicine and Biology)
Objectives. Until now, limited knowledge remains regarding the association among childhood obesity, cognitive behavior, and brain networks. Utilizing a publicly available dataset, we aimed to investigate the relationships between childhood obesity and functional networks during the stop-signal task. Results. Given the huge conflict-monitoring and inhibitory control demands of the task, both enhanced network connectivity and properties were observed under the “No-go” compared to the “Go” condition for both obese and non-obese preadolescents. Obese preadolescents exhibited significantly increased frontal-parietal, frontal-occipital, and frontal-temporal linkages, as well as heightened network efficiency under both “Go” and “No-go” conditions compared to non-obese counterparts. Additionally, significant correlations were found between network connectivity and properties and preadolescents’ body mass index (BMI), with their combination predicting BMI scores successfully. Conclusions. These findings support that childhood obesity is not simply a deviant habit with restricted physical health consequences, but rather associated with the atypical development of frontal-based networks involved in inhibitory control and cognitive performance.